2013
DOI: 10.1021/mp4005244
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Mediated Destruction of LHRHa-Targeted and Paclitaxel-Loaded Lipid Microbubbles Induces Proliferation Inhibition and Apoptosis in Ovarian Cancer Cells

Abstract: Although paclitaxel (PTX) is used with platinum as the first line chemotherapy regimen for ovarian cancer, its clinical efficacy is often limited by severe adverse effects. Ultrasound targeted microbubble destruction (UTMD) technique holds a great promise in minimizing the side effects and maximizing the therapeutic efficacy. However, the technique typically uses non-targeted microbubbles with suboptimal efficiency. We synthesized targeted and PTX-loaded microbubbles (MBs) for UTMD mediated chemotherapy in ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…tUCA vs. non-tUCA for enhanced drug delivery Strikingly, when tUCAs for drug delivery are directly compared with their non-targeted UCA counterparts, tUCAs are more efficient both in vitro [184,185,188,189,192] (up to 7.7-fold higher [189]) and in vivo [186,187,190,191] (up to 5-fold higher [186]), regardless of whether the drug was coadministered with the tUCAs or whether the drug was loaded on/in the tUCAs. Although the reasons for this higher efficiency have not yet been investigated, several could be possible.…”
Section: Enhanced Drug Deliverymentioning
confidence: 99%
“…tUCA vs. non-tUCA for enhanced drug delivery Strikingly, when tUCAs for drug delivery are directly compared with their non-targeted UCA counterparts, tUCAs are more efficient both in vitro [184,185,188,189,192] (up to 7.7-fold higher [189]) and in vivo [186,187,190,191] (up to 5-fold higher [186]), regardless of whether the drug was coadministered with the tUCAs or whether the drug was loaded on/in the tUCAs. Although the reasons for this higher efficiency have not yet been investigated, several could be possible.…”
Section: Enhanced Drug Deliverymentioning
confidence: 99%
“…PLMBs were fabricated as described previously [27]. OPLMBs were fabricated by a modified emulsification process [27,28].…”
Section: Preparation Of Ptx-loaded Mbs (Plmbs) and Oxygen And Ptx-loamentioning
confidence: 99%
“…OPLMBs were fabricated by a modified emulsification process [27,28]. Five milligrams of 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (Avanti Polar Lipids Inc., Alabaster, AL, USA), two milligrams of 1,2-distearoyl-sn-glycero-3- The PTX loaded MBs (PLMBs) were prepared by replacing oxygen and perfluoropropane gas with perfluoropropane gas only in the above recipe.…”
Section: Preparation Of Ptx-loaded Mbs (Plmbs) and Oxygen And Ptx-loamentioning
confidence: 99%
See 1 more Smart Citation
“…We have encapsulated perflourocarbon compounds (PFC) in liposome MBs and loaded the MBs with paclitaxel (PTX) for UTMD-mediated drug delivery. Our previous in vitro and in vivo studies have demonstrated that the UTMD process can effectively enhance the PTX deposition at the disease site and improve the therapeutic outcome [14,15]. We have also delivered oxygen and PTX simultaneously for combination therapy in hypoxic ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%